CONGESTION CONTROL REAL-TIME PATH PLANNING IN HYBRID VANET FOR URBAN AREA - Mohan, Meera; Antony, Deepthi (IJRDO -Journal of Computer Science Engineering, 2015)
Real time path planning algorithm is an effective way to avoid traffic congestion in urban areas. It is challenging to develop an algorithm for path planning as each driver has their own preferences while driving. There is existing Hybrid Intelligent Transportation System (ITS) for path planning and it is hybrid VANET enhanced ITS. This system utilizes vehicular ad-hoc network and cellular systems of public transportation systems. With the help of this system, it is possible to have a real time communication between vehicles, road-side units (RSUs) and vehicle-traffic server. This system improves overall spatial utilization of a road network and reduces average vehicle travel cost by avoiding it from getting stuck in traffic congestion. This is achieved by using real time path planning algorithm. Proposed system improvises the path planning algorithm by selecting the right path by considering the criticality of the vehicle (for e.g., ambulance) and the type of the vehicle (a two wheeler can use a narrow path when compared to the path that can be used for a car). By this approach, travel cost should come down and also the spatial utilization should be even better than existing system